An Overview of NATO Air Operations in Libya - M. T. El Gimati-Gimat, youesf; G. M. El-Krghli, Sabri (Scientific Journal of University of Benghazi, 2026)
This paper seeks to achieve three main objectives: (1) to determine the sum of air sorties and air strike sorties conducted by NATO alliance in Libya over the period April to October. (2) To discover the nature and the number of targets destroyed. (3) To find out which parts of Libya have the largest number of destroyed targets over this period. In terms of research methodology, data were collected from NATO main website. The analysed data presents a seven months period of air operation undertaken by NATO. In this study, descriptive statistical analysis was used. The main variables considered are: date of operation, total sorties, total strike sorties, vicinity, number of targets destroyed and type of targets. One-way analysis of variance (ANOVA) or Kruskal-Wallis (KW) tests were used to examine the research hypotheses. The key findings are: (1) approximately 36.4% from the total sorties are total strike sorties. (2) Significant difference among the seven months was noticed. (3) High efficiency and effectiveness were detected throughout the seven months of air operations as air operations decreased and targets destroyed increased. (4) The main focus of NATO activities was to destroy storages, resupplying facilities and heavy weapons. The value of this paper can be seen from the following points: (1) the study is pioneering as none has conducted such research. (2) The study might be seen as an objective indicator to assess NATO operations effectiveness and efficiency in performing its mission. (3) The results emerged might be compared with other studies conducted elsewhere in the world to extract some key inference; Finally, the paper concludes by acknowledging some research limitations and suggesting a number of advanced areas of research.